The leaf development process and its significance for reducing self-shading of a tropical pioneer tree species - Yamada, Toshihiro; Okuda, Toshinori; Abdullah, Makmom; Awang, Muhamad; Furukawa, Akio (Springer, 2000)
On a monoaxial erect stem of trees with continuous leafing, the older leaves would be quickly shaded by newer (upper) leaves if the trees did not have any compensating mechanisms to avoid self-shading. We hypothesized that the dynamic adjustment of leaf deployment, by regulating the patterns of leaf growth and by changing leaf orientation as leaves age, is a compensating mechanism. To verify this hypothesis, we analyzed leaf development and crown structure of a Far Eastern tropical pioneer tree species, Macaranga gigantea (Rub. f. et Toll.) M.A., which unfolds huge leaves directly on a monoaxial stem with a short leafing interval. Petioles required more than 90 days for full elongation and the petiole angle (the angle between the petiole axis and the vertical) increased over time. Thus, a series of leaves on a stem progressively increased in petiole length and petiole angle from the youngest to the oldest leaves. This is beneficial because it decreases the degree of self-shading within a crown. A simulation suggested that an average crown for the M. gigantea seedlings, which was constructed using empirically determined morphometric data cannot entirely eliminate self-shading within the crown. But an average crown had a lower degree of selfshading, with less dry mass allocation to the petiole than simulated crowns that were identical to the average crown in all but one respect: They had constant petiole lengths or petiole angles. We conclude that M. gigantea seedlings reduce self-shading by regulating elongation of the petiole and changes in the petiole angle with increasing leaf age.